Molecular Determinants and Pharmacological Analysis for a Class of Competitive Non-transported Bicyclic Inhibitors of the Betaine/GABA Transporter BGT1 - Kickinger, Stefanie; Lie, Maria E. K.; Suemasa, Akihiro; Al-Khawaja, Anas; Fujiwara, Koichi; Watanabe, Mizuki; Wilhelmsen, Kristine S.; Falk-Petersen, Christina B.; Frølund, Bente; Shuto, Satoshi; Ecker, Gerhard F.; Wellendorph, Petrine (Frontiers in Chemistry, 2021)
The betaine/GABA transporter 1 (BGT1) is a member of the GABA transporter (GAT) family with still elusive function, largely due to a lack of potent and selective tool compounds. Based on modeling, we here present the design, synthesis and pharmacological evaluation of five novel conformationally restricted cyclic GABA analogs related to the previously reported nanomolar potent and selective BGT1 inhibitor (1S,2S,5R)-5-aminobicyclo[3.1.0]hexane-2-carboxylic acid (bicyclo-GABA). Using [3H]GABA radioligand uptake assays at the four human GATs recombinantly expressed in mammalian cell lines, we identified bicyclo-GABA and its N-methylated analog (2) as the most potent and selective BGT1 inhibitors. Additional pharmacological characterization in a fluorescence-based membrane potential assay showed that bicyclo-GABA and 2 are competitive inhibitors, not substrates, at BGT1, which was validated by a Schild analysis for bicyclo-GABA (pKB value of 6.4). To further elaborate on the selectivity profile both compounds were tested at recombinant α1β2γ2 GABAA receptors. Whereas bicyclo-GABA showed low micromolar agonistic activity, the N-methylated 2 was completely devoid of activity at GABAA receptors. To further reveal the binding mode of bicyclo-GABA and 2 binding hypotheses of the compounds were obtained from in silico-guided mutagenesis studies followed by pharmacological evaluation at selected BGT1 mutants. This identified the non-conserved BGT1 residues Q299 and E52 as the molecular determinants driving BGT1 activity and selectivity. The binding mode of bicyclo-GABA was further validated by the introduction of activity into the corresponding GAT3 mutant L314Q (38 times potency increase cf. wildtype). Altogether, our data reveal the molecular determinants for the activity of bicyclic GABA analogs, that despite their small size act as competitive inhibitors of BGT1. These compounds may serve as valuable tools to selectively and potently target BGT1 in order to decipher its elusive pharmacological role in the brain and periphery such as the liver and kidneys.